The variability of the water temperature field in Antarctica by data of the passing measurements on the R/V “Akademik Fedorov” in 1999-2011 - Ju. V. Artamonov; N. N. Antipov; V. P. Bunjakin; A. V. Klepikov; V. A. Litvinov; V. V. Lukin; E. A. Skripaleva (Ukrainian Antarctic Journal, 2012)
The results of investigation of sea surface temperature (SST) interannual variability using the data of the passing measurements, carried out on zonal tacks around Antarctic continent during the expeditions on the R/V “Akademik Fedorov” in 1999-2010 are presented. The spatial features of SST anomalies in navigation areas, which are compared with SST anomalies, calculated on archive data, are described. The results are analyzed from position of display of climatic variations in the ocean-atmosphere system with typical periods 2-7 years.